Movie Still From The Pearl - RKO Radio Pictures:::Creator::::::::::::
The Pearl movie still of the Doctor (Charles Rooner) taking breakfast in bed from servant (unknown actress.) A Caption reads: THE PEARL The rich doctor refuses to see the baby. This scene filmed in Acapulco de Juarez, Guerrero, Mexico, North America. RESTRICTED USE Original in safe